Spiritual Quotient as an Extending the TAM Model: Gen Z Muslim’s Intention to Use Islamic E-Wallet - Rahmawaty, Anita; Taufikin, Taufikin; Astutik, Puji (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores the role of Spiritual Quotient (SQ) in adopting Islamic e-wallets using the Technology Acceptance Model (TAM) approach. The data for this research were obtained from 130 Gen Z Muslim users of Islamic e-wallets in Central Java, Indonesia. The research data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings of this study reveal that spiritual quotient and perceived benefit have a positive and significant influence on the intention to use Islamic e-wallets. However, perceived usefulness and perceived ease of use do not significantly affect the intention to use. Through this research, Islamic e-wallet service providers can further enhance system performance, effectiveness, and ease of use to build higher service credibility.